Chapter Sl.eccl. мудрость. Studi per un lexicon plurilingue dei termini religiosi e filosofico-teologici - Romoli, Francesca (Biblioteca di Studi Slavistici, 2018)
The article aims at defining the semantics of Church Slavonic мудрость as it emerges from medieval and pre-modern Eastern Slavic sources (from 12th to 18th c.). Occurrences were verified in the historical sub-section of the Russian National Corpus. Elaboration of the collected data is directed at delineating the range of meanings of the term and evaluating its possible semantic variations. For the multilingual lexicon of religious and philosophical-theological words, the results of the inquiry are so disparate as to favor a return to the individual sources over meanings derived from dictionaries.